2018
DOI: 10.1021/acs.jmedchem.7b01282
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of an Orally Bioavailable Inhibitor of Defective in Cullin Neddylation 1 (DCN1)-Mediated Cullin Neddylation

Abstract: We previously reported the discovery, validation, and structure-activity relationships of a series of piperidinyl ureas that potently inhibit the DCN1-UBE2M interaction. We demonstrated that compound 7 inhibits both the DCN1-UBE2M protein-protein interaction and DCN1-mediated cullin neddylation in biochemical assays and reduces levels of steady-state cullin neddylation in a squamous carcinoma cell line harboring DCN1 amplification. Although compound 7 exhibits good solubility and permeability, it is rapidly me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 61 publications
4
36
0
Order By: Relevance
“…The reasons behind the disparity in in vitro activity between DI-591 and NAcM-OPT is not fully understood, given the compounds similarity in proposed mechanism of action. In vivo work has shown that NAcM-OPT is orally bioavailable and has a half-life of 4.2 h in mice [71]. These data provide evidence that NAcM-OPT may have therapeutic value, particularly in cancers with elevated levels of DCN1.…”
Section: Nacm-optmentioning
confidence: 69%
“…The reasons behind the disparity in in vitro activity between DI-591 and NAcM-OPT is not fully understood, given the compounds similarity in proposed mechanism of action. In vivo work has shown that NAcM-OPT is orally bioavailable and has a half-life of 4.2 h in mice [71]. These data provide evidence that NAcM-OPT may have therapeutic value, particularly in cancers with elevated levels of DCN1.…”
Section: Nacm-optmentioning
confidence: 69%
“…Recent reports have described the development of novel small molecules endowed with selective pharmacologic modulation of the N-terminal acetylation-dependent regulatory interaction of UBE2M with DCN1 (DCUN1D1/SCCRO) [ 51 , 52 ], a regulatory subunit of the multiprotein E3 ligase for the ubiquitin-like protein NEDD8. This allows a more targeted and nuanced activity relative to the complete ablation of neddylation afforded by MLN4924 or other NEDD8 E1 inhibitors, with preferential selectivity toward CUL1 and CUL3 [ 52 , 53 ]. Based on these premises, we investigated the activity of the pharmacologic inhibitor of DCN1-UBE2M complex, NAcM-OPT, a small molecule with high level of selectivity for inhibition of DCN1 over the highly homologous human DCN isoforms [ 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…This allows a more targeted and nuanced activity relative to the complete ablation of neddylation afforded by MLN4924 or other NEDD8 E1 inhibitors, with preferential selectivity toward CUL1 and CUL3 [ 52 , 53 ]. Based on these premises, we investigated the activity of the pharmacologic inhibitor of DCN1-UBE2M complex, NAcM-OPT, a small molecule with high level of selectivity for inhibition of DCN1 over the highly homologous human DCN isoforms [ 52 , 53 ]. As shown in Supplementary Figure 6A,B and F,G , treatment of SKO-007(J3) cells with NAcM-OPT (micromolar concentration range, previously shown to be effective in cell-based studies [ 52 ]), significantly increased cell surface expression of MICA and MICB, as detected by flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The structural analysis of the DCN1-UBC12 interaction suggests that this interaction is amenable for structure-based design of DCN1 inhibitors. Guy et al identified piperidinyl urea based DCN1 inhibitors after screening a library containing 601,194 compounds [10][11][12]. Of these compounds, NAcM-OPT effectively interrupted the DCN1-UBC12 interaction (IC 50 = 80 nM).…”
mentioning
confidence: 99%